Organisational Stress and Employee Dissatisfaction at Work: A Case Study to Boost Employee Satisfaction - Goel, Upma (Journal of Commerce and Trade, 2014)
Employee satisfaction is the terminology used to describe whether employees are happy and comfortable and fulfilling their desires and needs at work. Many measures purport that employee satisfaction is a factor in employee motivation, employee goal achievement, and positive employee morale in the workplace.Employee satisfaction, while generally a positive in your organization, can also be a downer if mediocre employees stay because they are satisfied with your work environment.Employee satisfaction or job satisfaction is, quite simply, how content or satisfied employees are with their jobs. Employee satisfaction is typically measured using an employee satisfaction survey. These surveys address topics such as compensation, workload, perceptions of management, flexibility, teamwork, resources, etc. This paper tries to identify the various measures for increasing employee satisfaction at work.